Antifungal attributes of Trichoderma harzianum in the control of charcoal rot of cowpea caused by Macrophomina phaseolina - R.O. ADETUYI, D.B. OLUFOLAJI*, M.A. AJAYI and (Indian Phytopathology, 2016)
Macrophomina phaseolina (Tassi) Goid. is a soil-borne pathogen that causes charcoal rot infection (damping-off) in legumes and cereals. Trichoderma harzianum, an endophyte was evaluated as biocontrol agent against cowpea charcoal rot disease in-vitro and in-vivo. In the in-vitro experiment, the antagonist inhibited the mycelial growth of M. phaseolina in all the treatment methods. The highest percentage inhibition was recorded on 72 hours prophylactic inoculation of T. harzianum and the lowest was recorded on 72 hours curative inoculation with 93.3% and 29.4% respectively. The higher the number of days the antagonist had established itself, the higher the mycelial growth inhibition on the pathogen. The percentage seed germination and seedling establishment revealed that the control (0 conidia/ml of T. harzianum) and 108 conidia/ml were significantly higher (p < 0.05) from 105 conidia/ml and 103 conidia/ml. The disease incidence and severity, were significantly higher (p < 0.05) in the control than the seed treated with the antagonistic fungus.